Conservative treatment of ankle sprain according to a recent literature - Kaźmierczak, Urszula; Kwiatkowski, Szymon; Radzimińska, Agnieszka; Strojek, Katarzyna; Weber-Rajek, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Due to complicated structure of ankle, it is exceptionally susceptible to injuries, of which one of the most common is a sprain. The sprain involves soft-tissue injuries that, depending on their level of seriousness, are categorized as first-, second- or third-degree sprains. The main goals of rehabilitation in the acute phase after the injury include reduction of pain, swelling and hematoma, as well as prevention from secondary injuries. During the subacute phase the emphasis should be put on restoring the joint’s function and its range of motion, as well as on gentle loading of the joint. Proprioception training, strength and stretching exercises should also be introduced. The next stage, during which the reconstruction of the damaged tissues takes place, involves the implementation of gradual progressive loading and the variety of earlier introduced procedures. In the final phase of rehabilitation, it is vital to reassure that the patient is able to return to full activity, especially if he or she is an athlete. Therefore, functional testing such as the Dorsiflexion Lunge Test or The Star Excursion Balance Test may be of help. The main predisposing factor for an ankle sprain is a previous injury of the same type. It is due to the fact that such an injury leads to impaired proprioceptive function and impaired postural control. Improper rehabilitation or the lack of thereof may cause the development of chronic ankle instability, which substantially reduces the chances of physical activity and the patient’s quality of life. The implementation of adequate preventive measures based on employing external stabilisers and neuromuscular training appears to be essential. The objective is to regain a good sense of proprioception as well as muscle reaction time within the ankle joint.